From intuition to data-informed decisions with Business Intelligence in Tymphany Czech Republic - Matúš, Libor; Potančok, Martin; Stanovská, Iva; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2021)
The aim of this thesis is to initiate discussion in Tymphany CZ (TYM CZ) organization about future role of data in decision making process. Throw practical project to prepare basic data and analytics environment in TYM CZ. To show on practical example how organisation could transform company culture from intuition to data-informed decision-making process which should lead to higher profitability of organisation (data added value). The author will step by step describe business model and business environment of TYM CZ including critical processes and KPIs, describe current system architecture and major obstacles with reporting and working with data, intuition-based model. One of the major tasks is to show new view how to work with data in future and increase future quality of data. Finally, to show proposals for improvement in current reporting and visualization. Present how right data (ad hoc accessible) in real time can support right business decision in TYM CZ, decrease time for data collection, verification, and reporting – automatization. Based on all above to proof that move from intuition to data informed decision is unavoidable.
Vedoucí práce: Martin Potančok
Závěrečná práce - Institut celoživotního vzdělávání (MBA)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet